THE CYCLOTRON EMISSION OF ANISOTROPIC ELECTRONS IN THE X-RAY PULSARS - Baushev, A. N.; Bisnovatyi-Kogan, G. S. (Одеські астрономічні публікації, 2017)
The spectrum of cyclotron radiation is calculated for anisotropically distributed relativistic electrons with a nonrelativistic velocity scattering across the magnetic field. It is shown that if such electrons are responsible for a formation of the "cyclotron" line in the spectrum of Her X-1, then the value of its magnetic field (3 - 6) x 1010 Gs following from this interpretation is in a good agreement with some other observations and theoretical estimations. Observations of a time dependence of the energy of this "cyclotron" line in the spectra of several X-ray pulsars is explained by a variability of the average longitude energy of the electrons, decreasing with increasing of the luminosity due to radiational braking of the accretion flow.